CALCULUS NOTES, EXERCISES & TUTORIALS - Nurhana Mohamad (Penerbit UTHM, 2023)
Generally, this book is a student learning guide for the Calculus course offered at the Center for Diploma Studies, Universiti Tun Hussein Onn Malaysia (UTHM). This book aims to help students to know and understand the concepts, calculation and evaluation conducted in Mathematics education in technical and analytical terms that need to be applied in various forms of problem solving for Calculus course.